Endoscopic evaluation of otitis and its management in dogs - Reshmi P (Department of Veterinary Surgery and Radiology,College of Veterinary and Animal Sciences, 2010)
The study was carried out in twelve clinical cases of dogs of either sex with history of affection of ear canal of different breeds and age groups presented to the Veterinary Hospitals of College of Veterinary and Animal Sciences at Mannuthy and Kokkalai to evaluate the endoscopic changes of the ear canal associated with otitis and its management.